Mathematical methods for physicists - Arfken, George B. (George Brown), 1922- (Academic Press, 1995)
This new and completely revised Fourth Edition provides thorough coverage of the important mathematics needed for upper-division and graduate study in physics and engineering. Following more than 28 years of successful class-testing, Mathematical Methods for Physicists is considered the standard text on the subject. A new chapter on nonlinear methods and chaos is included, as are revisions of the differential equations and complex variables chapters. The entire book has been made even more accessible, with special attention given to clarity, completeness, and physical motivation. It is an excellent reference apart from its course use.